PENGARUH KEAKTIFAN DAN MINAT BELAJAR TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN DASAR-DASAR MANAJEMEN PERKANTORAN DAN LAYANAN BISNIS KELAS X MPLB DI SMK NEGERI 1 PEMATANGSIANTAR T.A 2024/2025 - Richard Victor S. Sinaga; Munajat (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The problem investigated in this study is that the majority of class X MPLB students at SMK Negeri 1 Pematangsiantar have not yet achieved the Learning Completion Criteria (KKTP). Out of a total of 107 students, only 38% succeeded in reaching KKTP, while the remaining 62% have not met the established standards. This condition indicates that most students are facing difficulties in achieving learning objectives, which suggests that there are obstacles in the learning process that impact student learning outcomes. This study aims to examine the influence of student activity and interest in learning on student learning outcomes in the subject of Fundamentals of Office Management and Business Services for class X MPLB at SMK Negeri 1 Pematangsiantar for the 2024/2025 academic year. The type of research used is ex-post facto with a population of all students in class X MPLB. The sampling technique used is purposive sampling, so a total of 71 students were selected as research samples, namely all students from class X MPLB 2 and X MPLB 3. The data collection techniques used in this study are documentation and questionnaire distribution, with the data analysis method conducted using multiple linear regression analysis using the SPSS 25 program. Before the questionnaire is used, a validity test and a reliability test are conducted first. The conclusion obtained is that the results of the partial hypothesis test show that activity has a positive and significant influence on learning outcomes, as does students' interest in learning. From the multiple linear regression test, the regression equation obtained is Y = 80.410 + 0.488 (X1) + 0.099 (X2) + ????, where activity has a greater influence, and the coefficient of determination R² is 94.5% on the learning outcomes of the Basics of Office Management and Business Services students, while 5.5% is influenced by other factors outside this study.